Genetic Polymorphisms in a 1.2 kb Long Fragment within Intron 2 of Chicken UBTD2 Gene - Zhang, H.Y.; Yang, W.J.; Luo, Y.Z.; Han , J.L. (International Journal of Poultry Science, 2013)
The widely expressed chicken UBTD2 gene in different types of tissues from embryonic to adult developmental stages implies its important role in regulating protein ubiquitination and delivery of ubiquitinated substrates, however, there is no specific study on the genomic DNA structure and function of chicken UBTD2 gene except a few invalidated SNPs derived from ESTs. In this study, a 1.2 kb long fragment within intron 2 of chicken UBTD2 gene was amplified and directly sequenced from a flock of 11 White Leghorn chickens. A total 15 sequences were identified from these birds, of which seven were homozygous but the remaining four were heterozygous. These new sequences were analyzed together with the homologous region in Gallus gallus reference genome version 71.4 (Chromosome 13: 8104760 - 8105979 in Galgal4). There were 10 polymorphic sites including seven transitions and three transversions, which defined four haplotypes in these 16 sequences. The Gallus gallus reference sequence formed a specific and distinct haplotype while the White Leghorn chickens carried three haplotypes at very similar frequencies of four, five and six sequences each. These data were the first piece of evidence of genetic polymorphisms present in the chicken UBTD2 gene which is therefore warranted for further investigation on the functional diversity in its complete genomic DNA sequence of different genetic backgrounds.